Tyrant or victim : reflections of Queen Min and Empress Dowager Cixi in modern theatre. - Nurkhalisah Kassim. (2011)
Both highly controversial figures in their nation’s history, Empress Myeongseong, otherwise known as Queen Min, and Empress Dowager Cixi have been deemed the villains and the cause of their nation’s downfall after their reign. Clearly, both Empress Dowager Cixi and Empress Myeongseong stood out from their contemporaries in terms of their political involvement and how they refused to fit into the typical mould of a royal consort. Both came from humble backgrounds, yet they were able to successfully climb up the ranks of their husband’s harem to be the first in power among the ladies of the imperial household. However, in the musicals The Last Empress and Forbidden City: Portrait of An Empress, the lives of both empresses have been portrayed in a more positive perspective which highlights their humanity and the struggles they underwent for the maintenance of their nation. As this essay studies the similarities and differences between the reflections of both empresses in the musicals, it will also seek to suggest answers as to why a new light is being shed onto these two figures in modern theatre.